The Methylene Blue Adsorption by Calcium Alginate-Activated Carbon Composite in Fixed Bed Column - Wardana Putra, Adzikri; Hermawan, Heru; Setyaningrum, Sinta; Paramitha, Tifa (Department of Chemical Engineering, Politeknik Negeri Bandung, 2024)
Methylene blue is a material that is often used as a cationic dye in the textile industry. Methylene blue is toxic and difficult to degrade. Adsorption is one method to reduce the methylene blue from wastewater. In this study, methylene blue was adsorbed by calcium alginate/activated carbon composite (CaAlg-AcC) in a fixed bed column. The influence of CaCl2.2H2O concentration, initial concentration of methylene blue, and flow rate in the continuous adsorption process were investigated. Every adsorption process was done in 110 min. The results revealed that the CaAlg-AcC composite synthesized using 1% (w/v) CaCl2.2H2O solution has the highest adsorption percentage, 95.28% in 110 min. The initial methylene blue concentration 50 mg/L gave the highest result of adsorption percentage with the smallest amount of methylene blue adsorbed of 31.77 mg. The flow rate of methylene blue 4 ml/min reached the highest adsorption percentage with the amount of methylene blue adsorbed of 41.79 mg.